InSAR grounding line mapping with the TSX/TDX/PAZ constellation for fast Antarctic glaciers - Krieger, Lukas; Floricioiu, Dana (2023)
The grounding line positions of Antarctic glaciers are needed as an important parameter to assess ice dynamics and mass balance in order to record the effects of climate change to the ice sheets as well as to identify the driving mechanisms for these. In order to address this need, ESA’s Climate Change Initiative (CCI) produced interferometric grounding line positions as ECV for the Antarctic Ice Sheet (AIS) in key areas. Additionally, DLR’s Polar Monitor project focuses on the generation of a near complete circum-Antarctic grounding line. Until now these datasets have been derived from interferometric acquisitions of ERS, TerrasSAR-X and Sentinel-1. Especially for some of the faster glaciers, the only available InSAR observations of the grounding line have been acquired during the ERS Tandem phases (1991/92, 1994 and 1995/96). In May 2021, a joint DLR-INTA Scientific Announcement of Opportunity was released which offers the possibility of a joint scientific evaluation of SAR acquisitions of the German TerraSAR-X/TanDEM-X and the Spanish PAZ satellite missions. These satellites are almost identical and are operated together in a constellation therefore offering the possibility of combining their acquisitions to SAR interferograms. The present study harnesses the interferometric capability of joint TSX and PAZ acquisitions in order to reduce the temporal decorrelation between acquisitions. The revisit times are reduced from 6 days (Sentinel-1 A/B) or 11 days (TSX) to 4 days (TSX-PAZ). Together, the higher spatial resolution than Sentinel-1 and the reduced temporal baseline allows imaging the grounding line at important glaciers and ice streams where the fast ice flow causes strong deformation. These are often the glaciers where substantial grounding line migration has taken place or is suspected (e.g Amundsen Sea Sector) but where current available SAR constellations cannot preserve enough interferometric coherence to image the grounding line. The potential of short temporal baselines was already shown with data ...